Diagnosis of Vitality in Skin Wounds in the Ligature Marks Resulting From Suicide Hanging. (September 2017) - Legaz Pérez, Isabel; Falcón, Maria; Gimenez, M.; Diaz, F. Martínez; Pérez-Cárceles, M.D.; Osuna, E.; Nuno-Vieira, D.; Luna, A.
Abstract : Abstract: Ascertaining the vital origin of skin wounds is one of the most challenging problems in forensic pathology. The forensic literature describes biomarkers and methods for differentiating vital and postmortem wounds, although no clear conclusions have been reached. The aim of this study was to characterize human vital wounds by analyzing the concentrations of metallic ions and the expression of P-selectin and cathepsin D in skin wounds in the ligature marks in a cohort of suicidal hangings for which vitality was previously demonstrated. A total of 71 skin wounds were analyzed within a postmortem interval of 19 to 36 hours. The concentration of Fe, Zn, Mg, and Ca and the expression of P-selectin and cathepsin D were analyzed together and separately. The majority of autopsied suicidal hangings were men (86%) with complete hanging mode (60.7%) in which there was a high frequency of subcutaneous injuries (78.3%). High concentrations of Ca and Mg compared with Fe and Zn were found. Ca and Zn concentrations decreased, and Fe concentration increased with the seriousness of the injury. A high percentage of moderately negative expression of both proteins was correlated with subcutaneous injury and low or medium concentrations of Fe. In conclusion, the joint study of metallic ions and proteins allows to characterize and to differentiate an injured vital wound of noninjured skin, especially when the damage in the tissue affects to the majority of the structures of the skin, but these results will need to be complemented with other biomarkers in time-controlled samples to further help in the differentiation of vital and postmortem wounds.